Three-Dimensional Simulation of Balloon Dynamics by the Immersed Boundary Method Coupled to the Multiple-Relaxation-Time Lattice Boltzmann Method (Communications in Computational Physics, 2018)
The immersed boundary method (IBM) has been popular in simulating fluidstructure interaction (FSI) problems involving flexible structures, and the recent introductionof the lattice Boltzmann method (LBM) into the IBM makes the method moreversatile. In order to test the coupling characteristics of the IBM with the multiple-relaxation-timeLBM (MRT-LBM), the three-dimensional (3D) balloon dynamics, includinginflation, release and breach processes, are simulated. In this paper, some keyissues in the coupling scheme, including the discretization of 3D boundary surfaces,the calculation of boundary force density, and the introduction of external force intothe LBM, are described. The good volume conservation and pressure retention propertiesare verified by two 3D cases. Finally, the three FSI processes of a 3D balloondynamics are simulated. The large boundary deformation and oscillation, obviouselastic wave propagation, sudden stress release at free edge, and recoil phenomenaare all observed. It is evident that the coupling scheme of the IBM and MRT-LBM canhandle complicated 3D FSI problems involving large deformation and large pressuregradients with very good accuracy and stability.